Diversity of Rotavirus Strains in Children; Results From a Community-Based Study in Nepal - Shrestha, Jasmin; Shrestha, Sanjaya K.; Strand, Tor A.; Dudman, Susanne; Dembinski, Jennifer L.; Vikse, Rose; Andreassen, Ashild K. (Frontiers in Medicine, 2021)
Objective: The objectives of this study were to describe the incidence and genetic diversity of Rotavirus (RV) infection among children up to 3 years of age in a community in Nepal. Methods: We investigated community-acquired cases of asymptomatic and symptomatic RV infections in children from birth to 36 months of age in a community-based birth cohort in Bhaktapur, Nepal. Monthly surveillance and diarrheal stool samples were collected from 240 children enrolled at birth, of which 238 completed the three years of follow-up. Samples were screened for rotavirus by Enzyme Immuno Assay (EIA). All RV screened positives were further genotyped by reverse transcription-polymerase chain reaction for the capsid genes VP7 and VP4. Results: In total, 5224 stool samples were collected from 238 children, followed from birth to 36 months of age. Diarrhea occurred in 92.4% (230/238) of all children in the cohort. During the 3 years study period, RV was more frequently seen in children with symptoms (7.5%) than in non-symptomatic children (0.8%). The highest RV detection rate was found in younger children between 3 and 21 months of age. Although rotavirus is known as winter diarrhea, it was detected throughout the year except in August. The highest positivity rate was observed in the months between December and March, with a peak in January. Four common G types were seen: G2 (30%), G1 (29%), G12 (19%) and G9 (16%). The most predominant genotypes seen were G2P[4] (30%), followed by G1P[8] (27.0%), G12P[6] (14.0%), G9P[8] (10%) and remaining were mixed, partial, and untyped. Conclusion: Our study confirms that rotavirus is a common cause of gastroenteritis in young children in the community. The prevalence and pathogenicity of rotavirus infection differed by age. There was substantial variability in circulating strains in the community samples compared to samples collected from hospitals. This shows the importance of including community-based surveillance systems to monitor the diversity of circulating rotavirus strains in Nepal.